Origin of Blue Hole Structures in Coral Reefs: Houtman Abrolhos, Western Australia - Wyrwoll, K.; Zhu, Z.; Collins, Lindsay; Hatcher, B. (CERF, 2006)
The distinctive blue hole terrains of the Houtman Abrolhos reef complex have been previously interpreted as the result of karst processes controlling Holocene reef growth and morphology. The apparent intensity of karst modification,indicated by the abundance and density of blue holes, steered the general perception of the reef complex as one that was stressed and marginal for Holocene coral growth. This view is commensurate with the high-latitude location (288 298 S) of the reefs. Through an investigation of the reef morphology, litho and seismic stratigraphy, and the growth chronology of these reef complexes, we demonstrate that the blue hole terrains of the Houtman Abrolhos are not karst features but are growth forms that are characteristic of these reefs.